2005
DOI: 10.2165/00019053-200523030-00005
|View full text |Cite
|
Sign up to set email alerts
|

International Variation in Resource Utilisation and Treatment Costs for Rheumatoid Arthritis

Abstract: Recent years have witnessed substantial progress in understanding the cost implications of rheumatoid arthritis (RA). To assess the divergent methodologies and their impact on the resulting cost analyses in RA, we conducted a systematic literature review to summarise the scientific evidence of RA-induced costs. Sixty-five reviews, models or cost analyses on the burden of illness and general costs associated with RA were identified. They covered the US, Canada, Sweden, the UK, The Netherlands, Germany and Finla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 72 publications
1
15
1
1
Order By: Relevance
“…Our estimates were higher than in earlier studies among RA patients [10,[29][30][31][32]. This is most likely due to the frequent episodes of morning stiffness in the inclusion criteria of our study sample.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Our estimates were higher than in earlier studies among RA patients [10,[29][30][31][32]. This is most likely due to the frequent episodes of morning stiffness in the inclusion criteria of our study sample.…”
Section: Discussioncontrasting
confidence: 88%
“…The ability of patients to remain in the active work force varies considerably between countries [16], although the survival in work seems to follow the same pattern [21]. Earlier studies have reported large variation in costs due to RA [10,[29][30][31][32]. A review article estimated the average annual cost of RA in Europe to be 13,500€ [10].…”
Section: Introductionmentioning
confidence: 99%
“…There are also a number of reviews available comparing different studies [29][30][31]; hence we will review the available literature only briefly.…”
Section: The Economic Burden Of Ramentioning
confidence: 99%
“…The direct cost of RA has been most widely studied in the US, and Table 3 presents a selection of these studies, derived mostly from the review by Rosery et al [31] with costs inflated to 2006 price levels using the US consumer price index. The analysis did not reveal any clear trend in the development of total direct cost over time.…”
Section: The Economic Burden Of Ramentioning
confidence: 99%
“…Η µελέτη αυτή επιβεβαίωσε τις εκτιµήσεις άλλων µελετών από άλλες χώρες και ήταν η πρώτη εκτίµηση του κόστους σε σχέση µε την βαρύτητα της νόσου στην Γαλλία. Υπάρχουν πολλές οικονοµικές εκτιµήσεις, από µελέτες οι οποίες είχαν σαν στόχο το κόστος, διαφορετικές βασικά στο αντικείµενό τους, στον τρόπο εκτίµησης, στο δείγµα τους, στον επιπολασµό τους, στην µεθοδολογία τους και στην ανάλυσή τους (Kobelt G 2006, Rosery H 2005. Αυτές οι µελέτες και το γεγονός ότι διεξήχθησαν σε διαφορετικές χώρες κάνουν αδύνατη την σύγκριση µεταξύ των αποτελεσµάτων τους.…”
Section: ρευµατοειδής αρθρίτιδαunclassified